PENGEMBANGAN KOMPETENSI PERANGKAT DESA DALAM PENGELOLAAN ASET DESA (Studi di Desa Pendem Kec. Janapria Kab. Lombok Tengah dan Desa Lingsar Kec. Lingsar Kab. Lombok Barat) - Abdul Manan (Sekolah Tinggi Pariwisata Mataram, 2021)
This study aims to describe the pattern of developing village apparatus competence in village asset management, and to explain the constraints to developing village apparatus competence in Village Asset Management. This research was conducted in Pendem Village, Kec. Janapria Kab. Central Lombok and Lingsar Village, Kec. Lingsar Kab. West Lombok. This research uses qualitative research. Furthermore, the data explored include primary and secondary data. The method used to determine the source of data in this study is purposive sampling. Data collection techniques were carried out with observation guidelines, interview guidelines and documentation analysis. Based on the results of the study that (1) Development of Village Apparatus Competence in Village Asset Management, village apparatus competence in managing village assets in both villages, namely 1) Pendem Village Kec. Janapria, Central Lombok Regency; and 2) Lingsar Village, Kec. Lingsar Kab. West Lombok, so far it is still limited to carrying out routines, they still do not have understanding, skills, and interests in the implementation of village asset management; (2) The obstacles faced in developing the competence of village officials in managing village assets, among others, are the busyness of the Village Head who is more focused on things that are considered more important, still lack of data, lack of facilities, lack of budget and lack of cooperation. among village officials.